The Role of Indonesian Language Teachers in Implementing The Pancasila Student Profile - Julianto, Indra Rasyid (PT Ilmu Inovasi Nusantara, 2024)
This article seeks to explore the role of Indonesian language teachers in implementing the Pancasila student profile. In this context, Indonesian language teachers are responsible for guiding the learning process, ensuring that moral values are conveyed and can be applied by students in both school and community settings. The younger generation today is facing a decline in morals and local wisdom, driven by the rapid advancement of globalization. This trend could lead to a loss of national character or identity among the youth, which requires special attention to address these issues and foster an understanding of good character within the educational framework. The classroom learning process must be of high quality to effectively support positive representations of Pancasila values, such as devotion to God, independence, critical thinking, creativity, cooperation, and global diversity. This study uses a descriptive qualitative approach and literature review, referring to sources related to the role of Indonesian language teachers in incorporating the Pancasila learner profile into Indonesian language education. The materials presented by Indonesian language teachers can integrate the Pancasila learner profile into various competencies, focusing on noble character, independence, critical thinking, cooperation, creativity, and diversity.